Phenotypic differentiation does not affect tumorigenicity of primary human colon cancer initiating cells - Dubash, Taronish Dorab; Hoffmann, Christopher M.; Oppel, Felix; Gießler, Klara Monika; Weber, Sarah; Dieter, Sebastian M.; Hüllein, Jennifer; Zenz, Thorsten; Herbst, Friederike; Scholl, Claudia; Weichert, Wilko; Werft, Wiebke; et al. (Cancer letters, 2016)
Within primary colorectal cancer (CRC) a subfraction of all tumor-initiating cells (TIC) drives long-term progression in serial xenotransplantation. It has been postulated that efficient maintenance of TIC activity in vitro requires serum-free spheroid culture conditions that support a stem-like state of CRC cells. To address whether tumorigenicity is indeed tightly linked to such a stem-like state in spheroids, we transferred TIC-enriched spheroid cultures to serum-containing adherent conditions that should favor their differentiation. Under these conditions, primary CRC cells did no longer grow as spheroids but formed an adherent cell layer, up-regulated colon epithelial differentiation markers, and down-regulated TIC-associated markers. Strikingly, upon xenotransplantation cells cultured under either condition equally efficient formed serially transplantable tumors. Clonal analyses of individual lentivirally marked TIC clones cultured under either culture condition revealed no systematic differences in contributing clone numbers, indicating that phenotypic differentiation does not select for few individual clones adapted to unfavorable culture conditions. Our results reveal that CRC TIC can be propagated under conditions previously thought to induce their elimination. This phenotypic plasticity allows addressing primary human CRC TIC properties in experimental settings based on adherent cell growth.
Available online 8 December 2015
Gesehen am 28.04.2020